2018
DOI: 10.3168/jds.2017-13910
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of non-aureus Staphylococcus spp. from heifer intramammary infections and body sites

Abstract: The purpose of this study was to investigate non-aureus Staphylococcus spp. intramammary infections (IMI) in periparturient heifers and determine the relationship of precalving body site isolation with precalving IMI and postcalving IMI using molecular speciation and strain-typing methods. Primiparous heifers were enrolled at approximately 14 d before expected calving date. Precalving mammary quarter secretions and body site swabbing samples (teat skin, inguinal skin, muzzle, and perineum) were collected. Post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 56 publications
3
46
0
Order By: Relevance
“…Some NAS species tend to be more relevant for the udder health, e.g. S. chromogenes [8,37,38]. This was substantiated in the current study as in herd 1, only milk samples from quarters with a SCC > 50 000 cells/mL milk and clinical signs harbored S. chromogenes.…”
Section: Nas Speciessupporting
confidence: 81%
See 1 more Smart Citation
“…Some NAS species tend to be more relevant for the udder health, e.g. S. chromogenes [8,37,38]. This was substantiated in the current study as in herd 1, only milk samples from quarters with a SCC > 50 000 cells/mL milk and clinical signs harbored S. chromogenes.…”
Section: Nas Speciessupporting
confidence: 81%
“…Non-aureus staphylococci (NAS), a heterogeneous group of bacteria, are the most frequently identified bacteria in bovine milk samples worldwide [1][2][3][4]. They are also colonizing the teat apex of both lactating and dry cows [5,6] as well as the teat canal [7] and other body parts [8]. We recently reported that Staphylococcus (S.) agnetis, S. auricularis, S. chromogenes, S. cohnii, S. epidermidis, S. equorum, S. haemolyticus, S. hominis, S. kloosii, S. rostri, and S. xylosus can also be isolated from rectal feces [9], indicating cows are shedding NAS into the environment which could eventually give rise to the establishment of intramammary infection (IMI), most likely after colonization of the teat apices.…”
Section: Introductionmentioning
confidence: 99%
“…This finding has also been demonstrated for other host-adapted staphylococcal species, specifically Staphylococcus aureus (Roberson et al, 1994). Furthermore, in one study, 44% of all heifers with a S. chromogenes IMI around the time of parturition had the same strain of S. chromogenes isolated from a body site, with many originating from the teat skin (Adkins et al, 2018). Although S. chromogenes IMI has been linked to elevated milk SCC and persistent IMI (Supré et al, 2011;Fry et al, 2014), isolation of S. chromogenes from the prepartum teat end has been associated with an SCC of <200,000 cells/ mL and may protect against IMI in early lactation (De Vliegher et al, 2003).…”
Section: Introductionmentioning
confidence: 56%
“…Identification of some staphylococcal species on the teat end has been found to be associated with IMI. Specifically, finding S. chromogenes on the teat skin of late-term heifers has been shown to significantly increase the odds of S. chromogenes IMI around the time of parturition (De Visscher et al, 2016a;Adkins et al, 2018). This finding has also been demonstrated for other host-adapted staphylococcal species, specifically Staphylococcus aureus (Roberson et al, 1994).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation